LOW DOSES OF FENOXAPROP-P-ETHYL CAUSE HORMESIS IN LITTLESEED CANARYGRASS AND WILD OAT - ABBAS,T. (2016)
ABSTRACT Hormetic effects of herbicides at ultra-low doses have been proved against range of crop species, although available data of herbicides hormesis about the weeds growth is very limited. This study investigates the promotive effect of low doses of fenoxaprop-Pethyl on growth and seed production of littleseed canarygrass and wild oat. Pot experiments were conducted twice in Wire House at Agronomic Research Area, University of Agriculture, Faisalabad, during 2014-15. Seven different concentrations of fenoxaprop-P-ethyl [0, 1, 3, 6, 9, 12 and 15 g a.i. ha-1] were applied as post emergence herbicide at 3-4 leaves stage of the weeds. Results revealed that increase in growth occurred within first two weeks after spraying at fenoxaprop-P-ethyl doses 1, 3 and 6 g a.i. ha-1. More growth stimulation as compared to all other treatments was observed at fenoxaprop-P-ethyl dose 6 g a.i. ha-1. This initial increase in growth sustains with time up to the maturity of both weeds and positively influences seeds production ability. Up to 28% and 17% increase in number of seeds per plants were occurred in littleseed canarygrass and wild oat, respectively. Doses above 6 g a.i. ha-1 negatively affect the weeds growth and seed production ability.